INTERNALIZATION OF RELIGIOUS MODERATION VALUE THROUGH SCHOOL CULTURE-BASED ACTIVITIES - Fauziah, Zumrotul (Universitas Nahdlatul Ulama Sunan Giri, 2021)
As a plural and multicultural country, conflicts frequently happened in Indonesia, it can be caused by the difference of race, ethnics, and also religion. This is certainly alarming. Therefore, there should be efforts to prevent the conflicts. This study aimed to describe efforts done by Islamiyah Malo Islamic senior high school in internalizing the religious moderation value through school cultural-based activities. The method used in this study is descriptive qualitative. Data in this research is gained through observation and interview. The result of the study shows that the internalization of religious moderation value in Islamiyah Malo Islamic senior high school is conducted through some cultural-based activities, such as: 1) socialization about the importance of relgious moderation values to the teachers and school staffs in very school meetings, 2) socialization about the importance of religious moderation value to the students through flag ceremony every Monday, 3) integrating religious moderation values in the process of teaching and learning, 4) literacy activity, 5) using momentum. Hopefully, from those activities, the students could have understanding anad knowledge about relgious moderation. So that they could be tolerant to any differences and be moderate in religious practices